ANALISIS FAKTOR PENANGANAN PANDEMI COVID-19, KINERJA OPERATOR, PERALATAN BONGKAR MUAT DAN EFEKTIVITAS LAPANGAN PENUMPUKAN TERHADAP PRODUKTIVITAS BONGKAR MUAT PETI KEMAS - Kurniawants Teguh Santoso; Achmad Fauzi; Andar Sri Sumantri (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
In this study, loading and unloading productivity is influenced by several factors including : handling of the Covid-19 pandemic, operator performance, loading and unloading equipment and stacking field effectiveness. These factors have an important role in increasing loading and unloading productivity. The population in this study were employees of PT. Salam Pacific Indonesia Lines Medan Branch with a total sample of 109 respondents. The data analysis used in this research is descriptive analysis and quantitative analysis, the data is analyzed using multiple linear regression analysis using the Application (SPSS) Version 25. The results of the t-test hypothesis testing indicate that the Covid-19 Pandemic Handling, Operator Performance, Loading and Unloading Equipment and Stacking Field Effectiveness partially positive and significant effect on loading and unloading productivity. Based on the results of the study, it is known that the research model of the multiple linear regression equation resulted in the following equation : Y = 0,329 + 0,177X1 + 0,178X2 + 0,231X3 + 0,380X4 + µ. From the equation results show that the Covid-19 Pandemic Handling variable (X1) has (t count 2,004 > t table 1,983), Operator Performance variable (X2) has (t count 2,085 > t table 1,983), the Unloading Equipment variable (X3) has (t count 2,467 > t table 1,983) and the Stacking Field Effectiveness variable (X4) has (t count 4,243 > t table 1,983). As for the value of Adjusted R2 = 0.604. This means that 60.4% of the variation in the dependent variable (Y), namely the Unloading Productivity is explained by the independent variables, namely the Covid-19 Pandemic Handling (X1), Operator Performance (X2), Loading and Unloading Equipment (X3) and Stacking Field Effectiveness (X4). The remaining 100% - 60.4% = 39.6%, influenced by other variables outside the study.